PENGARUH PEMBERIAN INFORMASI MELALUI MEDIA BOOKLET TERHADAP TINGKAT KEPATUHAN PASIEN DM TIPE 2 - Ni Ketut Puspita Sari; I Nyoman Sutresna; Alfiery Leda Kio; I Nyoman Ariyoga (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Adherence is a major component of successful diabetes treatment which is influenced by knowledge and skills regarding disease management. Providing information through health education using a multimedia approach can help patients to master information more effectively, one example is using booklets. This study purposed to determine the effect of providing information through booklet media on the compliance level of type 2 DM patients. This study used a pre-experimental method with a One group pre-test-posttest design. This study included 36 samples selected by purposive sampling technique. Data collection using questionnaires, data analysis consists of univariate and bivariate analysis. This study showed the most results were 29 people or 80.6% were less obedient during the pre-test and the most were 34 people or 94.4% were obedient during the post-test. The results of the Wilcoxon sign rank test obtained Zstats = 4,949> Ztable = 1.96 and P-value = 0.001 <α 0.05, this result can be concluded that the provision of information through the media booklet has a significant effect on the level of compliance of type 2 DM patients. It is recommended that the hospital use booklet media when providing information to type 2 DM patients about diabetes mellitus and its treatment therapy, so that the information conveyed can be easier to understand.